Strengthening of interpretation skills and problem solving through a virtual learning environment - Gutiérrez-Rodríguez, César Augusto (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article is the result of an applied quasi-experimental research, whose objective was to strengthen the competence of interpretation and problem solving from the subject of Technology and Information Technology, integrating the Information and Communication Technologies, ICT, in the teaching-learning process. The work started with 30 tenth grade students in an Educational Institution of Cali, Colombia. We used a Virtual Learning Environment, VLE, designed under the guidance of the didactic technique of Problem Based Learning (PBL). The initial characterization of the competition was made based on the result of the Saber 11/2015 tests, together with a diagnostic evaluation designed with questions from the Saber 9th grade test booklet. After implementing the VLE, the results of the final test indicate that the group improved the interpretation and problem solving competence, when comparing its performance with respect to the initial test. Likewise, positive changes were observed in the social and behavioral fields, which indicate that technological mediation produced a greater commitment of the students in their training process.